(untitled) (Scientific journal of the Fergana State University, 2025)
The article highlights the individual interpretations of the tree image—one of the ancient traditional symbols—in the poetry of female poets. Structural-poetic, historical-cultural, psychological, and hermeneutic methods were used during the research. The image of a tree is analyzed in the poems of Zulfiya, Halima Khudoyberdiyeva, and Enakhon Siddikova for its distinctive style and philosophical-emotional meanings. In their works, the image of a tree is psychologically linked to the image of a human being and expresses poetic meaning through parallelism. The renewed dimensions of the mythological image are revealed in Uzbek women’s lyrical poetry through the tree motif, along with expressions of the lyrical “I,” hope for the future, and unique interpretations of contemporary issues. The article also explores how various phenomena and objects are described in lyrical works in a way that reflects the poet’s perspective, bringing the author’s views to the foreground through depictions of specific events or items.